Muscle Cholesterol and Serum Biochemical Changes in Broilers Fed with Crude Rice Bran Oil - Anitha, B.; Moorthy, M.; Viswanathan, K. (International Journal of Poultry Science, 2007)
An experiment was conducted to study the inclusion of crude rice bran oil on production performance, carcass characteristics and biochemical parameters for a period of seven weeks with two hundred and sixteen commercial, straight run day-old Vencobb broiler chicks. These chicks were randomly grouped into six treatments with three replicates of twelve chicks each. The treatment groups consisted of 0% (T1), 1% (T2), 2% (T3), 3% (T4), 4% (T5) and 5% (T6) crude rice bran oil included in the broiler diet. The breast muscle cholesterol revealed no significant difference between treatment groups. Whereas the mean thigh muscle cholesterol of other treatment group birds was significantly (p<0.05) lower than those of control group. The serum total cholesterol, HDL cholesterol, LDL cholesterol and triglycerides level did not differ significantly between treatment groups.